2016
DOI: 10.1021/acs.jpcb.6b00909
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Induced-Fit Process Underlying the Activation of Apoptotic BAX by an Intrinsically Disordered BimBH3 Peptide

Abstract: Apoptotic BAX protein functions as a critical gateway to mitochondria-mediated apoptosis. A diversity of stimuli has been implicated in initiating BAX activation, but the triggering mechanism remains elusive. Here we study the interaction of BAX with an intrinsically disordered BH3 motif of Bim protein (BimBH3) using ESR techniques. Upon incubation with BAX, BimBH3 binds to BAX at helices 1/6 trigger site to initiate conformational changes of BAX, which in turn promotes the formation of BAX oligomers. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…NMR relaxation dispersion experiments showed that intrinsically disordered pKID binds KIX by the induced-fit mechanism with accumulation of an intermediate (Sugase et al 2007 ). Coupled folding and binding reactions by the induced-fit mechanism have also been reported for many other IDPs, including the transactivation domains (TADs) of c-Myc, Gal4, and VP16 (Ferreira et al 2005 ), CBD of WASP binding to Cdc42 (Lu et al 2007 ), IA 3 binding with YPrA (Narayanan et al 2008 ), S-peptide binding with S-protein (Kiefhaber et al 2012 ), N TAIL domain from Sendai virus nucleoprotein binding to phosphoprotein PX (Wang et al 2013b ; Dosnon et al 2015 ; Schneider et al 2015 ), PUMA binding with MCL-1 (Rogers et al 2014 ), BimBH3 binding with BAX (Jhong et al 2016 ), and STAT2 TAD binding with the TAZ1 domain of CBP (Lindstrom and Dogan 2017 ).…”
Section: Mechanisms Of Coupled Folding and Binding Of Idpsmentioning
confidence: 99%
“…NMR relaxation dispersion experiments showed that intrinsically disordered pKID binds KIX by the induced-fit mechanism with accumulation of an intermediate (Sugase et al 2007 ). Coupled folding and binding reactions by the induced-fit mechanism have also been reported for many other IDPs, including the transactivation domains (TADs) of c-Myc, Gal4, and VP16 (Ferreira et al 2005 ), CBD of WASP binding to Cdc42 (Lu et al 2007 ), IA 3 binding with YPrA (Narayanan et al 2008 ), S-peptide binding with S-protein (Kiefhaber et al 2012 ), N TAIL domain from Sendai virus nucleoprotein binding to phosphoprotein PX (Wang et al 2013b ; Dosnon et al 2015 ; Schneider et al 2015 ), PUMA binding with MCL-1 (Rogers et al 2014 ), BimBH3 binding with BAX (Jhong et al 2016 ), and STAT2 TAD binding with the TAZ1 domain of CBP (Lindstrom and Dogan 2017 ).…”
Section: Mechanisms Of Coupled Folding and Binding Of Idpsmentioning
confidence: 99%
“…This study used a 26-mer-long BimBH3-domain-based peptide (see Fig. 1d for sequence) to induce the activation of pro-apoptotic BAX protein and MOMP 18,[20][21][22] . Interactions of several BH3-only-based peptides with pro-survival proteins have been previously reported, showing that they would vary substantially in affinity with different peptide lengths and truncated forms of the proteins 14,[23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…BAX expression and purification. Full-length BAX and variants were prepared as previously described 18,22,35 . Mouse BAX was cloned into pTYB1 vector (New England Biolabs, Inc.), resulting pTYB1-BAX construct.…”
Section: Methodsmentioning
confidence: 99%
“…[21-24, 51, 52] This Gaussian-baseda pproach has also been utilized to capture intermediate conformationso fa ni ntrinsically disordered protein/peptide (IDP). [53] BH3 motif of Bim protein (BimBH3) is an IDP,b ut it is knownt ot rigger the apoptotic activation of BAX by binding to BAX at surface groove between helices 1 and 6. [54] To study the structuralc hanges of BimBH3 peptide, BAX and double-labeled BimBH3 were incubated together and snap-frozen in liquid nitrogen during the activation reaction, followed by DEER measurements on the samples trapped at different time points.…”
Section: Validation Of Heterogeneityi Nt He Tikr Distance Distributionsmentioning
confidence: 99%
“…[54] To study the structuralc hanges of BimBH3 peptide, BAX and double-labeled BimBH3 were incubated together and snap-frozen in liquid nitrogen during the activation reaction, followed by DEER measurements on the samples trapped at different time points. [53] The resultant distance distributions are highly heterogeneous for the mixtures of BimBH3a nd BAX, but they can be decomposed into individual components using the Gaussian-based approach( Figure 3B). The analysis revealed the change in the populations of structured and unstructured BimBH3p eptides at differentl engths of incubation time during the activation.Itwas shown that helical propensity of BimBH3i si ncreased upon binding to BAX but is then reduced after being released from the activated BAX due to large conformational changes between inactive anda ctive BAX.…”
Section: Validation Of Heterogeneityi Nt He Tikr Distance Distributionsmentioning
confidence: 99%